(De)Gendering Older Patients: Exploring Views on Aging and Older Patients in Romanian General Practitioners - Craciun, Catrinel (Universidad de Costa Rica, 2016)
Abstract. Purpose: Demographic changes make it necessary to improve communication with older patients and design gender sensitive health promotion. The present article aimed to explore how general practitioners see old age and what role gender may play in their representations of aging. It also looked whether the gender of the older patients played a role for how general practitioners treated them. Methods: Episodic interviews were conducted with 17 women and 17 men who worked as general practitioners in Romania. Thematic coding was used to analyze data. Results: Findings showed that general practitioners saw old age as negative no matter their gender. Older patients were perceived as difficult and mostly older women were given as negative examples to illustrate treatment non-adherence and psychological or social problems related to aging. Conclusion: Negative aging views combined with a (de)gendering of aging patients may lead to maintain negative aging stereotypes and gender inequality in old age. Implications for preventing this from happening are discussed.Resumen. Propósito: Los cambios demográficos hacen necesario mejorar la comunicación con pacientes mayores y diseñar promoción de la salud sensible al género. El presente artículo explora cómo médicos generales perciben la adultez mayor y qué rol puede jugar el género en sus representaciones sobre el envejecimiento. También examina si el género de los pacientes mayores jugó un rol en la forma en la que los médicos generales los trataron. Métodos: Se llevaron a cabo entrevistas episódicas con 17 mujeres y 17 hombres que trabajaron como médicos generales en Rumanía. Se usó codificación temática para analizar los datos. Resultados: Los hallazgos mostraron que los médicos generales ven la adultez mayor como negativa sin importar el género. Se percibió a los pacientes mayores como difíciles y se mencionó principalmente a mujeres como ejemplos negativos para ilustrar falta de adherencia al tratamiento y problemas psicológicos y sociales relacionados con el envejecimiento. Conclusión: Ejemplos de envejecimiento negativo combinados con una invisibilización del género de los pacientes puede guiar hacia el mantenimiento de estereotipos negativos sobre el envejecimiento y la desigualdad de género en la adultez mayor. Se discuten implicaciones para prevenir que esto pase.